Development of learning comic with Banjar culture on two variable linear equations system - Yun ita; Rahmatya Nurmeidina; Soraya Djamilah (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
Students experience difficulties in translating information presented in problem-solving tasks into appropriate mathematical models. Therefore, learning media are needed to help students solve problem-solving tasks more easily and contextually. This study aims to describe the development process, validity, and practicality of a Banjar Culture-based learning comic on the topic of a system of linear equations in two variables (SLETV). This study employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages Analysis, Design, Development, Implementation, and Evaluation. The research instruments consisted of validation and practicality sheets. The validation sheet was assessed by three validators, consisting of a lecturer experienced in developing mathematics learning comics, a mathematics teacher who teaches eighth-grade students, and a lecturer experienced in Banjar Culture-based research. The practicality sheet was completed by 22 students and one mathematics teacher. The data were analyzed using descriptive qualitative and descriptive quantitative techniques. The qualitative data were analyzed based on the comments and suggestions provided by the validators as a basis for product revision, while the quantitative data were analyzed using percentage scores to determine the levels of validity and practicality. The results showed that the comic obtained a validity score of 89.52%, categorized as very valid, and a practicality score of 94.45%, categorized as very practical. Therefore, the Banjar Culture-based learning comic was considered valid and practical and can be used in the learning process as well as for independent learning.